2002
DOI: 10.2320/matertrans.43.2789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu and Transition Metals on the Precipitation Behaviors of Metastable Phases at 523 K in Al-Mg-Si Alloys

Abstract: Morphology and crystal lattice of precipitates formed in the 6000 series Al-Mg-Si alloys containing Cu and transition metals of Cr and Fe (TM) after aging at 523 K were investigated by high-resolution transmission microscopy (HRTEM). The precipitates in the Cu-bearing alloys are more finely and densely distributed than those in the Cu-free alloys, whereas those in the TM-bearing alloys were coarser and formed inhomogeneously at the interfaces between the dispersoids and the matrix. Three kinds of metastable ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…6b). Potential phase is β'-Mg 1.8 Si (Table 2) present (for example) in Al-Mg-Si alloys containing Cu and transition metals [16]. Crystal structure of proposed phase is presented in Figure 7 (view in [001]).…”
Section: Resultsmentioning
confidence: 99%
“…6b). Potential phase is β'-Mg 1.8 Si (Table 2) present (for example) in Al-Mg-Si alloys containing Cu and transition metals [16]. Crystal structure of proposed phase is presented in Figure 7 (view in [001]).…”
Section: Resultsmentioning
confidence: 99%
“…In order to optimize the microstructure of Al-Mg-Si ingots prior to their extrusion, it is necessary to understand the high-temperature precipitation of these alloys during cooling from the solutionizing temperature [4][5][6]. In the case of the ternary Al-Mg-Si alloys without excess of Si, previous works [7][8][9][10][11][12][13][14][15][16] showed that the precipitation sequence is rather well established and can be described as follows: supersaturated solid solution ? GP zones ?…”
Section: Introductionmentioning
confidence: 99%
“…5 reveals that the age hardening is more prominent with Cu and Ag than Pt and Pd. Because Cu and Ag are important elements that facilitate the precipitation and keep the precipitates stable as known in normal coarse- grained samples, 18,20,25) it is suggested that they function in the same manner even in ultrafine-grained samples.…”
Section: Gb ð1þmentioning
confidence: 99%